Pulmonary sarcoidosis with dendriform ossification: Diagnostic and pathological insights - Smith, Hannah; Shilo, Konstantin; Singha, Arindam (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Pulmonary ossification is the histologic finding of mature bone with or without marrow elements within pulmonary tissue. The mechanism of formation is incompletely understood but thought to include metaplastic transformation of pulmonary fibroblasts to osteoblasts secondary to some form of chronic insult and the resulting inflammation from this insult. There are two classifications of pulmonary ossification, nodular and diffuse, based on histologic features. Management of pulmonary ossification is typically supportive, with treatment of the underlying process if one is identified. Here, we describe a man with known pulmonary sarcoidosis previously considered stable who presented with worsening dyspnea and was found to have pulmonary ossification and active cardiac and pulmonary sarcoidosis.